Working women’s work engagement and life satisfaction in Sabah, Malaysia: Marital status as the moderator - Elpidia Juli; Md Sayed Uddin; Trixie Marjorie Tangit (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2024)
Work engagement is a vital practice that should be encouraged among employees and employers, particularly within large companies or organizations. This importance arises from the fact that such entities typically have multiple divisions and sub-divisions, including departments and sections. Work engagement plays a crucial role in fostering effective teamwork among employees and employers across these various departments. While the interplay between work engagement and life satisfaction has been explored in both Western and non-Western studies, there is limited research on this topic within the context of Sabah, Malaysia. Moreover, research focusing on the relationship between work engagement and life satisfaction in Sabah remains relatively sparse. This study aims to investigate the role of marital status as a moderator in the relationship between dimensions of work engagement and dimensions of life satisfaction. A total of 348 female government servants participated in this research, which employed a snowball sampling method. Data collection was concentrated in the district of Kota Kinabalu, Sabah, Malaysia. Questionnaires, both online and physical, were distributed among the participants. The findings suggest that marital status moderates the relationship between work engagement and life satisfaction among female government servants in Kota Kinabalu. Furthermore, marital status partially moderates the relationship between their dedication to job responsibilities and their cognitive life satisfaction.